Towards a political reading of film: bringing together critical media literacy and political theory - Haus, Michael (heiEDUCATION journal, 2023)
This contribution asks how a ‘political reading’ of film can be conceptualized and how a critical film analysis can serve the purpose of democratic education and empowerment. For this, the discourse on critical media literacy (CML) serves as a reference, making clear that dealing critically with media means far more than questions of ‘truth’ and ‘harm prevention’. It also requires regarding media as sites of political struggle and a politics of representation. There are several sources and reference points for engaging in critical film analysis thus understood, reaching from the analysis of conditions of production over reception analysis to content analysis. The article also asks how political theory as an academic discipline can be used productively in this context. Going beyond activist and everyday understandings of politics, political theory might offer deeper political readings. Against that backdrop, a systematic distinction of different approaches for a political reading of film with the help of political theory is presented, with ‘raising awareness’, ‘situating politically’, ‘understanding concepts’ and ‘widening the horizon’ as four ideal types. Finally, practical implications are discussed with respect to two worlds of film: the ‘world of cinema’ and the ‘world of television’.
Gesehen am 12.09.2023